OPTIMASI NILAI YIELD DAN KARAKTERISASI SERBUK MUCILAGO DAUN KEMBANG SEPATU (Hibiscus rosa-sinensis Linn.) SEBAGAI GELLING AGENT - Hans Junifer Imanuel (2023)
Mucilago Hibiscus rosa-sinensis L. (MHR) is a primary metabolism in the leaf cell of Hibiscus rosa-sinensis L., which contains polysaccharides that can be used in pharmaceutical excipient. The study aims to optimize the yield value of MDKS isolution with complete factorial random design method and characterize the MDKS powder as gelling agent. Temperature (80, 85, and 90°C) and time (4, 5, and 6 hours) variations of MDKS isolation are used to see their impact on yield values. The ability of MDKS powder as gelling agent is demonstrated through an ibuprofen gel formulation evaluation with a HPMC comparison. The MDKS isolation result with temperature variations of 80°C over 4 hours has the highest yield value (7,16%±0,212). Two Way Anova test shows temperature and time variations affecting yield values (P<0,05) and then yield values increase with each temperature decrease and time. Characteristics of MDKS powder appropriate with gelling agent parameters, such as rheological properties (pseudoplastic anti-ticsotropic), swelling index (24x previous volume), and optical rotation (-130,46°±0,57). Evaluation of ibuprofen gel using MDKS powder as a qualified gelling agent except for non-translucent organoleptic. The optimal temperature for MDKS is ≤80°C. MDKS powder can be used as a gelling agent but produces a non-translucent color.